(untitled) (Research, Society and Development, 2021)
The forage spineless cacti are the main xerophilic crop grown in Brazil, however its growth and production may be influenced by the photochemical performance of Photosystem II, regardless of the cultivation system. In this context the objective was to evaluate the photochemical efficiency of Nopalea cochenillifera Salm-Dyck depending on ground cover at different schedules of evaluation. The research was carried out at the Pendência Experimental Station, belonging to the Paraibana Company for Research, Rural Extension and Regularization Landholding (EMPAER-PB), municipality of Soledade, state of Paraíba, Brazil. The treatments were distributed in randomized blocks, with three repetitions in the 2 × 4 factorial scheme, corresponding to the soil with and without mulch and four chlorophyll fluorescence evaluation times at, 08:00, 11:00, 14:00 and 17:00 hours. The variables analyzed were: initial fluorescence, variable fluorescence, maximum fluorescence, variable/initial fluorescence ratio and potential quantum yield. The use of mulch increased the maximum and variable fluorescence, especially in the first schedules of evaluation, photosystem II photochemical activity was highest at 17:00 hours.